Analysis overall equipment effectiveness (OEE) raw mill machine using DMAIC method in cement industry - Fathurohman, Dimas Mukhlis (Operations Excellence: Journal of Applied Industrial Engineering, 2025)
Equipment failure significantly impacts machine performance, leading to decreased productivity, increased repair costs, and reduced production output. PT XYZ, a company engaged in cement production, has been experiencing frequent downtime on the Raw Mill Plant 10 machine, resulting in abnormal production volumes and reduced efficiency. These issues contribute to the engine efficiency index remaining below the industry standard. To address these challenges, a comprehensive performance evaluation and improvement strategy is necessary. This study implements Total Productive Maintenance (TPM) by integrating the Overall Equipment Effectiveness (OEE) metric and applying the DMAIC (Define, Measure, Analyze, Improve, Control) methodology to identify and reduce inefficiencies. Additionally, a fishbone diagram is utilized to determine the root causes of the problem. The findings reveal that the OEE value for the Raw Mill machine is 80.78%, falling short of the 85% benchmark. Among the six big losses affecting equipment performance, speed losses account for 79.81%, making it the most dominant contributor to inefficiency. These results suggest the need for targeted improvements focused on minimizing speed-related disruptions, optimizing machine availability, and enhancing overall equipment performance to meet production targets and cost efficiency goals.